Embodying Mêtis: The Braiding of Cunning and Bodily Intelligence in Feminist Storymaking - Metta, Marilyn (University of Western Australia, 2015)
This paper playfully uses the terms mêtis and Metis to trace the act (the performative doing) and the art (the braiding) of bodily intelligence and cunning in feminist storymaking. To highlight the importance of mêtis/Metis in contemporary feminist scholarship and research methodology, I draw on my own research in embodied lifewriting and narratives of resistance in women’s lives as well as my recent project of re-mythologising the ancient Greek Goddess Metis and her embodiment of mêtis. The term mêtis refers to the quality of bodily intelligence and cunning whilst the term Metis refers to the ancient female mythological figure in Greek mythology. The term cunning is used in this paper as both a noun (the quality of resourcefulness, trickery and elusiveness) and an adjective. The term storymaking is used to suggest a kind of doing and an act of making something – it implies an active, conscious and deliberate act and process. The notion of storymaking also suggests how we make stories and how stories make us (see Metta 2010, 286). In its bridging of the discursive and the corporeal, I see this reclamation project of Metis/mêtis in feminist storymaking as an example of feminist materialist methodology.